2017
DOI: 10.1002/cctc.201701203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Carbon Monoxide Dissociation on a Cobalt Fischer–Tropsch Catalyst

Abstract: The way in which the triple bond in CO dissociates, a key reaction step in the Fischer–Tropsch (FT) reaction, is a subject of intense debate. Direct CO dissociation on a Co catalyst was probed by 12C16O/13C18O scrambling in the absence and presence of H2. The initial scrambling rate without H2 was significantly higher than the rate of CO consumption under CO hydrogenation conditions, which indicated that the surface contained sites sufficiently reactive to dissociate CO without the assistance of H atoms. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…58 By combining 12 C 16 O/ 13 C 18 O isotopic scrambling with in situ infrared spectroscopy, we have demonstrated earlier that direct CO dissociation proceeds predominantly on step-edge sites. 37 This is consistent with the expected strong structure sensitivity of the CO dissociation reaction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…58 By combining 12 C 16 O/ 13 C 18 O isotopic scrambling with in situ infrared spectroscopy, we have demonstrated earlier that direct CO dissociation proceeds predominantly on step-edge sites. 37 This is consistent with the expected strong structure sensitivity of the CO dissociation reaction.…”
Section: Discussionsupporting
confidence: 87%
“…The detailed preparation of this catalyst can be found in the literature. 37 The accessible surface area of 116.7 μmol of Co atoms/g of catalyst was determined by H 2 -chemisorption (ASAP 2010, Micromeritics). The average cobalt particle size of 15 nm was determined by TEM analysis (FEI Tecnai 20) and confirmed by in situ XRD (D/max-2600, Rigaku).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined above, we have demonstrated that direct CO dissociation on the same Co/SiO 2 catalyst is possible and can be correlated to a minority site at the surface. 53 Therefore, the minor increase in CO coverage will significantly influence the reaction kinetics. This scenario will be discussed in a companion paper.…”
Section: Resultsmentioning
confidence: 99%
“…30,4852 Although it is difficult to disprove an H-assisted CO dissociation mechanism on a surface that contains adsorbed CO and H, we have recently demonstrated by isotopic exchange of a 12 C 16 O/ 13 C 18 O mixture that CO dissociation is fast and reversible on an empty cobalt surface. 53 …”
Section: Introductionmentioning
confidence: 99%